2013
DOI: 10.1038/nm.3115
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic glucagon signaling inhibits hepatic glucose production

Abstract: Glucagon activates hepatic protein kinase A (PKA) to increase glucose production, but the gluco-stimulatory effect is transient even in the presence of continuous intravenous glucagon infusion. Continuous intravenous infusion of insulin, however, inhibits glucose production through its sustained actions in both the liver and the mediobasal hypothalamus (MBH). In a pancreatic clamp setting, MBH infusion with glucagon activated MBH PKA and inhibited hepatic glucose production (HGP) in rats, as did central glucag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 47 publications
4
124
1
Order By: Relevance
“…Hormones such as insulin, glucagon, and leptin have been shown to regulate hepatic glucose metabolism through both central and peripheral actions (34,35). In this study, we provide several lines of evidence demonstrating that the stimulatory effect of FGF21 on hepatic gluconeogenesis is mainly mediated by its central actions on hypothalamic neurons.…”
Section: Discussionmentioning
confidence: 68%
“…Hormones such as insulin, glucagon, and leptin have been shown to regulate hepatic glucose metabolism through both central and peripheral actions (34,35). In this study, we provide several lines of evidence demonstrating that the stimulatory effect of FGF21 on hepatic gluconeogenesis is mainly mediated by its central actions on hypothalamic neurons.…”
Section: Discussionmentioning
confidence: 68%
“…By contrast, activation of PKA in MBH inhibits HGP and resembles the effects of glucagon injection to the hypothalamus. The glucagon-induced activation of hypothalamic PKA and inhibition of HGP are both attenuated in rats fed a high-fat diet, whereas activation of PKA by Sp-cAMPS infusion to MBH can still efficiently inhibit HGP in these rats (Mighiu et al 2013). These findings suggest that hypothalamic glucagon resistance contributes to increased HGP and hyperglycemia in diabetes and obesity and that pharmacological activation of PKA in MBH can bypass the glucagon resistance with therapeutic potential for diabetes treatment.…”
Section: Camp/pka In the Brainmentioning
confidence: 84%
“…In hypothalamic neurons, cAMP signaling is modulated by several hormones including leptin and insulin to affect food intake (Zhao 2005). A recent study found that glucagon acts in the hypothalamus to inhibit HGP by a PKA-dependent mechanism (Mighiu et al 2013). Inhibition of PKA activity in the mediobasal hypothalamus (MBH) abolishes the suppressive effect of glucagon on HGP and leads to increased i.v.…”
Section: Camp/pka In the Brainmentioning
confidence: 99%
“…In addition to the central actions mentioned above, it has been suggested that the satiety effect of glucagon may involve the suppression of the orexigenic hormone ghrelin via the hypothalamic -pituitary axis (133) . It has recently been reported that hypothalamic glucagon signalling inhibits hepatic glucose production and that the central resistance to this hormone might be involved in the hyperglycaemia that characterises diabetes (134) . Considerable evidence supports the role of glucagon as a thermogenic agent, thereby favouring the body's energy expenditure.…”
Section: Effects Of Glucagon On Food Intake Body Weight and Body Energymentioning
confidence: 99%